EFFECT OF YISHENJIANPI RECIPE ON SEMEN QUALITY AND SPERM MITOCHONDRIA IN MICE WITH OLIGOASTHENOZOOSPERMIA INDUCED BY TRIPTERYGIUM GLYCOSIDES - Sheng, Wen; Zhang, Yao-Sheng; Li, Yue-Qing; Wu, Xiao-Ni; Chai, Li-Min; Yue, Li-Feng; Liu, Juan; Ding, Jin; Li, Xian-Rui; Chen, Meng; Shang, Jian-Wei (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background:Kidney tonifying - spleen strengthening method being one of the modalities for treatment ofastheno-oligozoospermia is currently commonly used in the clinical setting. To investigate the mechanism ofYiShenJianPi (YSJP) Recipe, used in Traditional Chinese Medicine to benefit “the kidney” and strengthen “the spleen”.Materials and Methods: Oligoasthenozoospermia, male BALB/c mice were randomly divided into normal control,disease model, positive control, low-dosage and high-dosage groups. Oligoasthenozoospermia was induced bytripterygium glucosides intragastric administration before treatment started.Through using computer-aided spermanalysis to test the changes in sperm quality, utilizing flow cytometry to test the percentage of sperm with normalmitochondrial transmembrane potential (JC-1 + %), utilizing X-ray microscopy to observe epididymal spermultra-microstructure placing special emphasis and photographing the differences in mitochondria of the flagellumregion.Results: Compared with DM, sperm quality of the treated mice was significantly better (P<0.05, respectively).Compared with PC, the LD group had significantly better quality sperms, while the parameters in the HD group werenumerically better. Compared with NC, all other groups had significantly lower percentage of sperms with normalmitochondrial membrane potential. In PC, LD and HD groups, the percentage of sperms with normal mitochondrialmembrane potential was significantly higher than that of D. The 9+9+2 mitochondrial sheath structure was complete inNC but damaged in DM. In the treatment groups, this structure was fairly clear.Conclusion: YSJP improved semen quality with oligoasthenozoospermia by improving sperm mitochondrialmembrane potential and restoring sperm mitochondrial ultrastructure.